Honeysuckle extracts as a potential inhibitor of SARS-CoV-2 infection - Lin, Ping-Chang; Lee, Ying-Ray; Liu, Li-Teh; Chiou, Shyh-Shin; Chen, Po-Chih; Tsai, Ching-Yi; Tsai, Jih-Jin (Frontiers in Pharmacology, 2025)
BackgroundIn the current era of coronavirus disease 2019 (COVID-19), we were interested in searching for medications other than the currently available antiviral drugs Paxlovid and Molnupiravir that cause minimal side effects and do not harm the human body. Honeysuckle extract (HSE) is a traditional Chinese medicine (TCM) that has been shown to exert antiviral effects in other studies. However, no studies have indicated whether HSE has an inhibitory effect on SARS-CoV-2.MethodsWe prepared HSEs from dried honeysuckle flowers. We performed a cell viability assay, median tissue culture infection dose (TCID50) assay, and qRT‒PCR, and calculated the virus titers using the Reed-Muench method to evaluate the inhibitory effects of aqueous and alcohol HSEs on SARS‒CoV‒2 and explore the possible underlying mechanisms.ResultsIn this study, post-treatment with HSE resulted in dose-dependent decreases in both the RNA levels and TCID50 of SARS-CoV-2 in Vero E6 cells; treatment with 50 μg/ml and 100 μg/ml alcohol HSEs achieved up to 95.323% and 92.587% inhibition, respectively. Moreover, pre-treatment with aqueous HSEs effectively reduced the RNA levels, and TCID50 of SARS-CoV-2 by up to 99.684%, and alcohol HSEs achieved up to 99.921% inhibition; both of these effects occurred in a dose-dependent manner.ConclusionThe results suggest that HSEs may have the potential to prevent SARS-CoV-2 infection.